Supporting and Prohibiting Factors in Reflective Case Discussion (RCD) - Suriyana, I Wayan Dedus; Sitoresmi, Hayyu (PT.Mantaya Idea Batara, 2021)
Reflective case discussion (RCD) is part of performance management development (PMD). RCD can be done in Hospital and Public Health Center.Nurses carried out RCD to discuss the Nursing issues and create a new Standard Operating Procedure (SOP) through reflective method. Objective: increase nurse professionalism and knowledge by holding discussions, sharing experiences so that mistakes in doing actions that have occurred do not happen again. All nurses must participate in RCD at least once a week. This activity was performed between half an hour and an hour. Method: Qualitative method with action research approach, involving 8 participants until the end in the operating room with three stages namely assessment, implementation and evaluation. Each stage is a reflective process, namely Plan, Action, Observe and Reflect stages. Results: This study found several themes regarding supporting factors, namely stakeholder support, and Nurse motivation, while inhibiting factors were lack of socialization and time and lack of evaluation and supervision. Conclusion: RCD did occur at Ibnu Sina Hospital because of lack of knowledge and socialization. Besides that, supervision and evaluation also did not work. The Head Nurse and Hospital management department must ensure that RCD activities are running and scheduled, because this activity is very important to improve the professionalism of nurses in their work as well as efforts to encourage the development of performance management.